Enhanced Solar‐to‐Hydrogen Generation with Broadband Epsilon‐Near‐Zero Nanostructured Photocatalysts. Issue 27 (8th May 2017) - Tian, Yi; García de Arquer, Francisco Pelayo; Dinh, Cao‐Thang; Favraud, Gael; Bonifazi, Marcella; Li, Jun; Liu, Min; Zhang, Xixiang; Zheng, Xueli; Kibria, Md. Golam; Hoogland, Sjoerd; Sinton, David; et al.
Abstract : The direct conversion of solar energy into fuels or feedstock is an attractive approach to address increasing demand of renewable energy sources. Photocatalytic systems relying on the direct photoexcitation of metals have been explored to this end, a strategy that exploits the decay of plasmonic resonances into hot carriers. An efficient hot carrier generation and collection requires, ideally, their generation to be enclosed within few tens of nanometers at the metal interface, but it is challenging to achieve this across the broadband solar spectrum. Here the authors demonstrate a new photocatalyst for hydrogen evolution based on metal epsilon‐near‐zero metamaterials. The authors have designed these to achieve broadband strong light confinement at the metal interface across the entire solar spectrum. Using electron energy loss spectroscopy, the authors prove that hot carriers are generated in a broadband fashion within 10 nm in this system. The resulting photocatalyst achieves a hydrogen production rate of 9.5 µmol h −1  cm −2 that exceeds, by a factor of 3.2, that of the best previously reported plasmonic‐based photocatalysts for the dissociation of H2 with 50 h stable operation. Abstract : A new scalable photocatalyst heterostructure based on a complex epsilon‐near‐zero nanoplasmonic material is designed and characterized. The resulting photocatalyst exhibits a stable production rate of hydrogen production of 9.5 µmol h −1 cm −2 . This performance exceeds, by a factor of 3.2, that of the best previously reported plasmonic‐based photocatalysts for the dissociation of H2 from water.